A COMPARATIVE STUDY OF DECLARATIVE SPEECH ACTS IN THE FATHER AND ELDERLY CARE PRACTICES IN THE LANTERA PROGRAM - R. Myrna Nur Sakinah; Yuyun Mulyati; Endang Sunandar; Nisa Febrianti Fatimah; Dewi Pujiastuti; Miftahul Maulana Kamal (Universitas Islam Negeri Sunan Gunung Djati, 2026)
This comparative mixed-method study examines declarative speech acts in elderly care communication across two contrasting contexts: the fictional portrayal in The Father by Florian Zeller and real-life interactions within the LANTERA program in Paseh, Bandung. This study is grounded in the theoretical framework of Pragmatics, particularly speech act theory. The research investigates how declarative functions such as informing, asserting, clarifying, reassuring, assigning roles, and expressing authority construct social meaning in caregiving. Data on fictional text are examined through discourse analysis, while data from the LANTERA program derive from questionnaires, observations, and semi-structured interviews, supported by descriptive statistics on respondents’ characteristics and communication patterns. Finding indicates both convergence and divergence between fictional and real contexts. In the fictional narrative, declaratives frequently reflect cognitive decline, power negotiation, and emotional tension, often producing ambiguity and disorientation. In contrast, LANTERA interactions emphasize clarity, politeness, and social harmony shaped by Sundanese cultural norms. Gender patterns appear in both settings: female caregivers tend to employ inclusive and mitigating declaratives expressing empathy, while male caregivers more frequently use assertive forms associated with authority and task orientation. The study highlights how linguistic choices mediate dignity, control, and relational balance in elderly care. The research recommends integrating culturally grounded communication training, empathy-oriented scripting, and monitoring of pragmatic quality to improve elderly services. By juxtaposing fiction and lived practice, the study underscores the value of literary representations as tools for reflecting on real-world caregiving discourse.